أثر الفضاءالسكني على التغير الاجتماعي للعلاقات الأسرية داخل المجتمع الجزائري - صبة, دلولة (Changement Social, 2018)
يشكل التغير الاجتماعي إحدى المواضيع التي شغلت اهتمام علماء الحقل الاجتماعي، وتركيزهم على دراسة مظاهر التباين والاختلاف في نظم البناء الاجتماعي للأفراد في ظل تنامي الاستخدام المفرط للتكنولوجيا. وبما أن الأسرة هي الخلية الأولى لهذا البناء، فإنها هي الأخرى تتأثر بالعوامل المادية واللامادية، ومن بينها العامل المعماري الذي يتخذ شكل الفضاء السكني، والذي يعد الوعاء الذي يحوي مجالاتها الوظيفية (مطبخ، غرفة) من جهة، ومن جهة أخرى يحوي مجالاتها الحيوية التي يتم فيها ممارسة الحياة اليومية والاجتماعية للفرد والأسرة ككل. ومن هذا المنطلق، -بحكم تخصصنا- نود معرفة العلاقة التبادلية بين العامل الفيزيائي (المبني) والعامل الاجتماعي (الأسرة)، أين نحاول في هذه الدراسة أن نسلط الضوء على أهم خصائص التنظيم الفراغي للمسكنوتأثيره على تغيير الرابط الأسري. وهذا بالاعتماد على اختيار أنماط سكنية مختلفة وفقا لتطور مدينة بسكرة، وفي مرحلة ثانية نقوم بتطبيق نموذج هول بطريقة مبتكرة لإعادة صياغة البنية المعمارية والاجتماعية، بغية دراسة أنماط المسافات الاجتماعية لأفراد الأسرة داخل المنزل. وهذا بالاعتماد على طريقة التحقيق الميداني وتطبيق تقنيات المقابلة،الملاحظة بالمشاركة والاستمارة. وبعد الوصول لنتائج الدراسة نقترح بعض توصيات العامة وتوجيهات العمرانية العلمية. وفق هذا المنظور يتم طرح التساؤل التالي: ما هو أثرالفضاءالسكنيعلى التغير الاجتماعي للعلاقات الأسريةداخل المجتمع الجزائري وفق منظور ادوارد هل ؟ الكلمات المفتاحية : نموذج ادوارد هول– مسكن – علاقات الأسرية– التغير الاجتماعي- التفاعل الأسري. The social change is the mosttopicsthattake the attention of modern sociologyat the time of technology. And theirconcentrated on the study of the difference, in systems of social structure of individual. The familyis the first cell of this structure, they are alsoaffected by the material and immaterialfactors, including architectural factor thattakes the form of residentialspace. The home container whichcontainsfunctional areas (room, kitchen) On the other hand, contains the vital areas of family and daily life practices in it. Fromthis point, by virtue of ourspecialty and wewouldlike to know the correlationbetween the physical factor (building) and the social factor, wherewe are trying in thispaperis to highlight the most important spatial organization of the analgesicproperties anditseffect on changing the familylink. And thisdepending on the choice of differenthousing styles according to the evolution of the city of Biskra, and in a second stage, weapply the Hall in an innovativeway to re-drafting of architecture and social model, aim to study of social distances patterns of familymembersinside the house. This way, we use investigative techniques as a questionnaire. Afteraccess to the results of the study, we propose somegeneralrecommendations and urbanscientific guidance.According to this perspective isasked the following question: Whatis the impact of the residentialspace for social change and family relations on Algerian society? Keywords: Model Edward Hall- housing– relationshipsfamily- social change–social interaction